1989
DOI: 10.1111/j.1151-2916.1989.tb06252.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Coarsening During Sintering of Boron Carbide

Abstract: The sintering behavior of boron carbide was investigated with particular attention given to microstructure development at various stages in the sintering process. Hot‐pressing and pressureless sintering techniques were employed and the effects of heating rate, firing atmosphere, and composition were used to characterize the sintering behavior. Pressureless sintering at temperatures up to 2300°C produces only limited densification. Microstructural coarsening is responsible for this since it leads to conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(103 citation statements)
references
References 12 publications
4
98
0
1
Order By: Relevance
“…In general, the final density increases with increasing sintering temperature and is hardly affected by the amount of free carbon. This observation agrees well with the results of Dole and Prochazka (10,11) who found that the density of B C becomes independent of the carbon addition above &4 wt% C. As shown in Fig. 3, post-densification by HIP to 100% of the theoretical density was possible with 2150 and 2175°C sintered materials having a sintered density *96% TD.…”
Section: Sintering and Hip Treatmentsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, the final density increases with increasing sintering temperature and is hardly affected by the amount of free carbon. This observation agrees well with the results of Dole and Prochazka (10,11) who found that the density of B C becomes independent of the carbon addition above &4 wt% C. As shown in Fig. 3, post-densification by HIP to 100% of the theoretical density was possible with 2150 and 2175°C sintered materials having a sintered density *96% TD.…”
Section: Sintering and Hip Treatmentsupporting
confidence: 93%
“…The role of carbon as a sintering aid in solid state sintering of B C is therefore twofold. First, during the early sintering stage, amorphous carbon inhibits coarsening, brought about by surface-to-surface matter transport (2), e.g., by suppressing vapor-phase transport via deoxidation (11).…”
Section: Microstructurementioning
confidence: 99%
“…10) Several previous studies have used reducing agents such as C 3),4) or He-H2 11) to react with and remove oxide impurities from the surface of boron carbide powder. According to the thermodynamic data, 12) Al gas is a reducing agent for boron oxide on B4C starting powder superior to carbon and/or He-H2.…”
Section: Resultsmentioning
confidence: 99%
“…Significant improvement in sinterability was observed when a small amount of carbon was added before hot pressing [1][2][3][4][5][6][7][8][9][10][11][12]. Other additives such as Al, Fe, Ti, B and SiC have also been used, with various degrees of improvement in sintering behavior and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%